Anorexia, Oral Health and Antioxidant Salivary System: A Clinical Study on Adult Female Subjects - Marco Mascitti; Erminia Coccia; Arianna Vignini; Luca Aquilanti; Andrea Santarelli; Eleonora Salvolini; Jacopo Sabbatinelli; Laura Mazzanti; Maurizio Procaccini; Giorgio Rappelli (MDPI AG, 2019)
The aim of this study was to compare the oral health status and salivary antioxidant system between patients diagnosed with anorexia nervosa (AN) and healthy controls. A total of 25 female AN patients and 25 matched healthy controls were enrolled. Clinical parameters and saliva samples were collected for each patient. Two questionnaires to investigate oral health and hygiene were administered. Superoxide Dismutase (SOD) activity and High Reactive Oxygen Species (hROS) were evaluated. Salivary concentration of SOD was significantly higher in subjects with AN compared with control group (1.010 ± 0.462 vs. 0.579 ± 0.296 U/mL; p = 0.0003). No significant differences between groups were identified for hROS (233.72 ± 88.27 vs. 199.49 ± 74.72; p = 0.15). Data from questionnaires indicated that, although most of the patients recognized the oral hygiene importance in maintaining a good oral health, more than half of them had poor oral hygiene. Altered biochemical composition of saliva in patients with AN could be interpreted as an effective defence mechanism against oxidative stress. Moreover, despite the discrepancy between clinical findings and perception of the oral health in AN population arose, the quality of life of these patients appears not to be significantly affected by their dental condition.